THE INFLUENCE OF PROJECT BASED LEARNING MODEL ON THE DANCE MOVEMENT CREATIVITY OF MANUK DADALI - Hana Pertiwi; Arsan Shanie (Jurnal Cakrawala Pendas, 2023)
This research was motivated by the lack of student creativity in dance lesson. The purpose of this study was to obtain the information related to the influence of Project Based Learning model on students' creativity in the field of dance lesson, namely Manuk Dadali traditional dance. This study was conducted at MI NU 56 Krajankulon, Kendal Regency, Central Java. The study design used Pre-experimental design of one group pre-test post-test of the PBL design. Performance and Documentation Test technique was used to collect the data evidences. Then, it continued with the analysis in the form of the normality test and the final analysis using the t-test (paired sample t-test). The results revealed that the average test before the PBL value is 56,34 and the average test after the PBL value is 65,46. These results were supported through the t-test results with a significance level of 0,05 and p = 0,000 < 0,05. Thus, it can be concluded that there is an influence of the Project Based Learning model to the creativity of students’ traditional dance lessons. Penelitian ini dilatarbelakangi dengan minimnya daya cipta siswa pada tarian masuk materi kapabilitas tari. Tujuan penelitian ini untuk mendeskripsikan model project based learning pada daya cipta siswa masuk bidang tarian daerah berupa manuk dadali. Jenis penelitian yaitu quasy eksperimen dengan desain peneltian yang digunakan dengan one group tes sebelum dilakukannya PBL-tes setelah dilakukannya PBL design. Sumber penelitian dengan data primer dan data sekunder. Teknik analisis data dengan t-test (paired sample t-test). Hasil penelitian didapatkan rerata skor tes sebelum dilakukannya PBL 56,34 dan rerata skor tes setelah dilakukannya PBL 65,46. Kesimpulan penelitian menunjukan bahwa terdapat pengaruh model project based learning terhadap daya cipta tari siswa.